(untitled) (American International Journal of Agricultural Studies, 2021)
Radishes (Raphanus sativus L) have high nutritive and medicinal values, and are predominantly cultivated in the temperate regions of the world. With the high malnutrition rate in Nigeria, domesticating radish is necessary. However, despite being successfully cultivated using the hydroponics system with cocopeat substrate in Nigeria, the adaption to the soil type is an important factor to consider. Seeds of three genotypes of radish were grown in cocopeat substrate and topsoil under rainfed and hand watering conditions. The experiment was set up as a 3 (genotypes) by 2 (substrates) by 2 (watering methods) factorial laid in a completely randomized design with three replicates. Data were collected on the plant height, number of leaves, leaf area, and the tuber and leaf weights respectively. Data collected were analyzed using ANOVA (SAS 9.0 version) and differences in treatment means were separated using least significant differences at 5 % significance level. Results obtained showed that the tuber weight of White Icicle Radish (21.35±3.32) was significantly heavier than the rest genotypes, and the hand watering system also encouraged the production of heavier tuber size (17.79±2.71) than the rainfed system (7.9.6±2.71). However, the planting substrate was insignificant in all parameters considered.